Corpo: trajetos e novos jeitos de ver e produzir o corpo na escola - Ludwig, Gilberto Luiz (2013)
An analysis as to how the body is dealt with in the school based on pedagogical and disciplinary practices. The first part deals with the philosophical heritage which is one the vectors which helped to forge the concept of the body in western civilization. The second part puts forth the Hebrew-Christian heritage which also sustains the practices of the western culture with regard to the body and corporeity. The third part concerns itself with the place and the treatment of the body in the school with its pedagogical practices. The discourse which has historically been elaborated around the body in a predominant and dominating way has always been one of subjugating the body, through disdain and discipline, to the dictates of those who hold the social-economic and political-cultural power. The school has become a faithful ally of this purpose. It is necessary, therefore, to recover concepts and practices which forged western civilization and to propitiate new approaches with regard to the body, changing current conceptions and practices, including, in the classroom, the recovery of the dignity of the body, the dignity of the human being.